Od „tronu świętego Jakuba” do patriarchatu jerozolimskiego - Paczkowski, Mieczysław C. (Vox Patrum, 2012)
The place of beginning of the Christian community was called „the Upper Church of the Apostles” in Mount Zion. It became the seat of the Mother Church under the leadership of fourteen bishops of Jewish stock from the beginning until the reign of Constantine. The authority of the bishops was symbolized by the throne of St. James. The complete transformation of Jerusalem into a „Roman city” operated by Emperor Aelius Hadrian meant the end of the Jewish hierarchy in the Mother Church and the emergence of a new leadership of Gentile origin. Until the time of bishop Maximus the Holy Sepulcher became the center of the Gentile Church. In the IV century we can say the growing rivalry between Caesarea and Jerusalem and appearing of many members of the hierarchy and the monastic communities participated very energetically in the problems of the local Church. In the time of Cyril of Alexandria can be seen the support given to him by the Palestinian bishops. The alliance Jerusalem – Alexandria would last until the beginning of the council of Chalcedon. At that time Juvenal of Jerusalem was striving for the recognition of patriarchal status for the see of the Holy City, decided to go over to the opposite side, formed by Constantinople, Rome and the Antiochenes, thus abandoning the „monophysite party”. Thanks to this dramatic change, the Church of the Holy Land was able to associate itself officially with the dogmatic decision of Chalcedon and the Metropolitan of Jerusalem was elevated to the status of Patriarch.